2013
DOI: 10.1080/10408398.2011.579361
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Probiotics on Risk Factors for Cardiovascular Diseases. A Review

Abstract: Probiotic microorganisms have historically been used to rebalance disturbed intestinal microbiota and to diminish gastrointestinal disorders, such as diarrhea or inflammatory bowel diseases (e.g., Crohn's disease and ulcerative colitis). Recent studies explore the potential for expanded uses of probiotics on medical disorders that increase the risk of developing cardiovascular diseases and diabetes, such as obesity, hypercholesterolemia, arterial hypertension, and metabolic disturbances such as hyperhomocystei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 168 publications
0
56
0
Order By: Relevance
“…For example, the fermentation of carbohydrates by the gut microbiota and probiotics results in the production of short chain fatty acids such as acetate or propionate which are used as energy in the host. 7 Studies also show that certain probiotic strains produce vitamin K, B2, B12, and folate, [61][62][63][64] all of which are utilized by the host. There are numerous examples showing the potential for probiotics to have a positive impact on the oral cavity, such as preventing dental caries, 65,66 decreasing halitosis, 67,68 and reducing episodes of streptococcal pharyngeal infections, 69 Teughels et al 70 recently showed that the daily usage of lozenges containing Lactobacillus reuteri by patients suffering from chronic periodontitis following standard dental scaling and root planing, resulted in significantly more pocket depth reduction and attachment gain in deep periodontal pockets, as well as a decrease in P. gingivalis levels.…”
Section: Application Of Probioticsmentioning
confidence: 99%
“…For example, the fermentation of carbohydrates by the gut microbiota and probiotics results in the production of short chain fatty acids such as acetate or propionate which are used as energy in the host. 7 Studies also show that certain probiotic strains produce vitamin K, B2, B12, and folate, [61][62][63][64] all of which are utilized by the host. There are numerous examples showing the potential for probiotics to have a positive impact on the oral cavity, such as preventing dental caries, 65,66 decreasing halitosis, 67,68 and reducing episodes of streptococcal pharyngeal infections, 69 Teughels et al 70 recently showed that the daily usage of lozenges containing Lactobacillus reuteri by patients suffering from chronic periodontitis following standard dental scaling and root planing, resulted in significantly more pocket depth reduction and attachment gain in deep periodontal pockets, as well as a decrease in P. gingivalis levels.…”
Section: Application Of Probioticsmentioning
confidence: 99%
“…Cardiovascular diseases (CVDs) have high mortality rates worldwide and have become a serious burden in many countries [1, 2]. Atherosclerosis (AS) is a progressive condition involving accumulation of lipids and fibrous elements in the large arteries, which is a key trigger for CVD [3].…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the present study are also of interest regarding the large body of literature on hypocholesterolemic effects of probiotic bacteria and the variety of mechanisms that have been proposed to explain those effects: incorporation of cholesterol into membranes, assimilation of cholesterol, decreased cholesterol synthesis or absorption, conversion of cholesterol to coprostanol and, most importantly, the bile salt hydrolase hypothesis [31][32][33][34][35] . Several reports have indicated that during growth, yeasts (Saccharomyces cerevisiae) can remove cholesterol from laboratory media supplemented with cholesterol [36,37] .…”
Section: Discussionmentioning
confidence: 94%